The Analysis of the Role of Science Subject Activator Teachers in the Success of Merdeka Belajar Program at SMP Muhammadiyah 1 Sidoarjo - Sulistianik, Sulistianik; Sartika, Septi Budi (Unnes Science Education Journal, 2024)
The purpose of this study is to analyze the role of the science subject teacher in the success of the independent learning program at the junior high school level. The research method used is a qualitative method of case study type. The research was conducted at SMP Muhammadiyah 1 Sidoarjo. The research conducted only focused on one science subject teacher at SMP Muhammadiyah 1 Sidoarjo. Data collection techniques used by researchers are questionnaires, interviews and documentation. From the data obtained, data analysis was carried out using three stages including data reduction, data presentation, and conclusion drawing. The results of this study found that the science teacher plays an important role in improving teacher competence as well as in student learning activities for the success of the independent learning program at the junior high school level which encourages the growth and development of teachers and students in implementing learning in accordance with the independent learning program. From the research that has been done, a science teacher has a role for teachers and students to be able to succeed in the independent learning program at the junior high school level. Further research is expected to find other efforts by science teachers that contribute to the success of Merdeka Belajar program.